Ethics of the Prosecutor’s Profession Related to Legal Fact Engineering in Indonesia - Taher, Tarmizi (Jurnal Scientia Indonesia, 2019)
The prosecutor as an institution conducting the task of prosecution and execution of court decision is expected to uphold its ethics as law enforcement profession. One of the prohibitions for prosecutors is the legal facts that have been regulated in the prosecutor's own regulation as set forth in the code of conduct of the prosecutor. Therefore, the prosecutors must obey the law corridor and obey the law. According to Chaeruddin Ismail, as a whole requires that every law enforcement institution really must have the values of integrity (integrity), fairness, respect for the constitution and governmental authority, honesty, courage ) and compassion so that every law enforcer can be wise and wise in responding to every different situation and condition. The prosecutor has 2 doors of supervision, externally and internally, and a clear procedure in enforcing the code of conduct of the prosecutor itself.